(untitled) (Fiep Bulletin - online, 2016)
Introduction: Metabolic syndrome (MetS) is a metabolic disorder associated with the production and accumulation of adipose tissue related to insulin resistance and release of inflammatory cytokines. IL-6 is an inflammatory cytokine produced in visceral adipose tissue and with high biological activity, adversely affecting lipid and glucose metabolism, creating a favorable environment for the development of cardiovascular disease (CVD). Methodology: Interleukin-6 was evaluated in 80 patients with MetS, 40 patients without CVD and 40 patients with established CVD, in a controlled cross-sectional study consisting of a historical sample of the database Outpatient Cardiometabolic Risk PUCRS. Results: Serum IL-6 levels were higher in patients with established CVD (P=0.036). The average age is higher in the group of patients without CVD (60±10 years). Were also statistically significant values of DBP (P=0.008), LDL cholesterol (P=0.026) in the group without CVD. For patients with CVD use of simvastatin is performed by most patients, showing statistical significance, respectively (P=0.001). Conclusion: Patients with MetS and with established CVD, showed serum levels of IL-6 higher, confirming its association with the development of CVD. These patients, even making use of statins also show levels of IL-6 increased, improving risk and probability of occurrence of new cardiovascular events.